Pembukaan Rekening Sambang Masjid BSI Sebagai Upaya Digitalisasi Pengelolaan Keuangan - Sidanatul Janah; Yopi Yudha Utama; Levina Puji Yuliani; Anggi Zulfika (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2024)
Currently, the mosque is not only a place of worship, but also a center of civilization for muslims. Because mosqueses can play a role as an effort to empower the community, improve the economy of the people, such as organizers of the Baitul Maal, Zakat, infaq and shodaqah service units. Digitizing mosque financial management makes it easier for Ta’mir to control incoming and outgoing funds. The research method used is a qualitatuve method in the form of literature. The mosque visiting program is a program in which BSI visits mosques in person and then asks about the conditions and environment around the ta’mir and mosque administrators, followed by asking how the mosque’s financial management is managed. Opening a sambang mosque account using easy wadiah savings. Digitizing mosque financial management makes it easier for ta’mir to control incoming and outgoing funds. By coming to save at the bank and if you want to see the results of the transaction, you can ask the bank for a checking account. And for people who want to donate or give alms, they can directly use the avaible Qris without having to open their wallet first.